DESIGN REVIEW ANALYSIS OF THE USE OF STONE HEAPS FROM STONE EXCAVATIONS IN THE PROBOLINGGO – BANYUWANGI TOLL ROAD CONSTRUCTION PROJECT SECTION 3 - Abdul Q, Muhammad Ali Hasymi; Witjaksana, Budi; Tjendani, Hanie Teki (Transpublika Publisher, 2024)
In constructing a toll road, the road structure will be carried out by constructing embankments on the road. However, in practice it often causes elevation differences between the two land surfaces, thereby increasing the risk of landslides. The objectives of the research are 1) Identifying the impact if Common Borrow Material (CBM) embankment work is replaced by rock embankment from excavation results, 2) Determine the value engineering process steps related to completing alternative design selection if there are differences between the actual Detailed Engineering Design in the field and 3) Determine the strategy and design optimization for volume differences which have implications for additional costs and project implementation time. The research uses a combination of quantitative and qualitative research methods. The data analysis technique is carried out using the Zero-one and Cost Analysis methods. The research results prove that 1) Implementation of the design review method for changes in common borrow material dumping work requires innovation to reduce cost elements and match performance and quality. 2) Solving problems using the design review method in the civil works construction phase where the Detail Engineering Design and actual field conditions have different stages of value engineering analysis. 3) Based on function analysis to optimize cost savings for work items using design review, a Preliminary Design according to DED Rp. 4,068,258,782,670 and Design after RE Rp. IDR 3,987,286,153,268 so the cost reduction after implementing the design review for the work of piling stones from stone excavation results is IDR 80,972,629,402.